Review on the Role of Agricultural Extension Service on Increasing Farm Productivity in Ethiopia - Argaw, Birhanu; Yehuala, Kalkidan; Aschalew, Alelign (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
Improving farm productivity either through introduction of modern technologies or by increasing agricultural extension services is vital. Agricultural extension is the primary mechanism that increases agricultural production. Therefore, reviewing the role of agricultural extension on increasing farm productivity has been interesting issue. Cognizant of this fact, reviewing the role of agricultural extension in increasing farm productivity is an important issue for policy makers in order to improve productivity. Consequently, this seminar was aimed to provide information on the role of agricultural extension in increasing farm productivity and to review agricultural extension constraints in Ethiopia. The review shows that agricultural extension service had positive and significant role on increasing farm productivity by increasing the farmer’s knowhow on agronomic practices such as pest and disease control and adoption of improved seed varieties as well as soil and water conservation technologies. On the other hand, the review reveals that weak interaction; low participation, lack of technical skills, missed use of services, the weak link of research extension, a lack of incentives, and a lack of suitable adaptation to technologies constrain the extension system across the country. Thus, based on the review the following recommendations are forwarded. Extension services should be increase to farmers by the government agents especially by district agriculture development unit, and NGO’s to assist farmers to have easy access to extension so as to increase farm productivity. In addition, to increase the current working conditions of extension agents, including transportation, housing, and proper budget allocation, the government should adopt a very responsible and practical approach.